Avaliação da cobertura do Sistema de Informações sobre Nascidos Vivos - SINASC, Minas Gerais - Anne Marielle Girodo (2015)
The purpose of this article consists in evaluate the coverage of Ministry of Health data systems on live births (SINASC) and also the degree of adequacy into its information for the state of Minas Gerais and macro-regions in order to analyze the consistency of this system and possible spatial divergence. The coverage was assessed using different methodologies for the state and the proactive search method of births in samples of Jequitinhonha’s Mesoregion municipalities. Besides the cover, with the inquire of proactive search it was possible to evaluate the contribution of possible sources of live births notification, supporting information that contribute to the development of this operating system. To assess the degree of coverage for all geographical regions of the state, it was compared the volume of live births reported to SINASC 2010 with the volume of births estimated from the Census data and its projections using the vital indicators adequacy assessment method (Andrade & Szwarwald), ranking the municipalities according to the 2010-2012 period information into: consolidated information, under consolidation phase or unconsolidated; the volume of live born reported to SINASC in 2010 was also compared to the volume estimated by Brass & Coale technique (1973). To evaluate the SINASC coverage of a sample of municipalities in the Jequitinhonha Valley, an proactive search was conducted on several sources of information, comparing the records of live births in 2008 reported to SINASC with those located in multiple sources. The results of this study are presented in the form of two articles. The first addresses the research of the active search and the second approaches the analysis of the information adequacy and coverage of macro- regions of Minas Gerais. The results present the deficiency in SINASC coverage in the Jequitinhonha Valley, with significant underreporting in municipalities (ranging from 7.9% to 70.2%), where the main potential sources of notification are notary’s office, hospitals and basic health units (covering 60 % of the records found by active search). Regarding the adequacy of live birth information, it was found that in the state, generally, 90% of municipalities presented consolidated information. However, when evaluating the population strata, it was found the existence of inequities regarding the consolidation of SINASC information, and areas with a high proportion of municipalities with poor information, as the case of municipalities with 50,000 or more inhabitants of South East geographical regions and North (33.3% and 20.0% of municipalities with deficient information). Regarding coverage, it was found that, depending on the method used for the estimates, the findings are different and can generate doubts about either the recommendation of the direct use of data from system or the use of indirect methods. Considering the evaluation of SINASC information adequacy and the coverage calculation based on primary data, it is expected to enhance the importance of the data generated by services and contribute to its improvement. By identifying municipalities with poor information, inequities are exposed, aspects which deserve investment in order to improve the quality of information are pointed, and, above all, incite the development of actions that contribute to overcome local limitations on the vital information systems.